Recent developments in manufacturing multiple emulsions using membrane and micro fluidic devices - Goran Vladisavljevic; Richard Holdich; Marijana M. Dragosavac; David A. Weitz (2010)
Membrane and microfluidic devices are new routes for controllable production of multiple emulsions with uniformly sized drops and accurate control of the internal drop structure. Membrane emulsification involves injecting single emulsion through a porous membrane into continuous phase in a stirred cell or cross-flow membrane module. In this work an alternative method to generate shear at the membrane surface was applied, based on the low frequency oscillation of the membrane at 10-90 Hz in a direction perpendicular to the flow of the injected phase. The advantage of oscillating membrane technique is that the risk of the drop breakage in the continuous phase is minimal, because the shear is generated only at the membrane surface. The oscillation signal was provided by an audio generator which fed a power amplifier driving the electro-mechanical oscillator on which the inlet manifold was mounted. The membrane was a microsieve-type membrane with regular pore spacing formed by Ni electroforming. At the constant maximal shear stress at the membrane surface the mean size of oil globules in W/O/W emulsions decreased with increasing the amplitude of oscillation. The most narrow drop size distribution with a span of 0.36 was obtained at 70 Hz and the peak amplitude of about 0.4 mm. A disadvantage of membrane emulsification is that the internal drop structure cannot be accurately controlled. Microfluidic devices with co-axial glass microcapillaries developed in Weitz Lab have been found convenient for controllable generation of both core-shell drops and multiple emulsion drops with a controlled number of inner drops in the outer drop. In this work core-shell drops with a size between 50 and 150 μm have been produced at the production rate ranging from 1,000 to 10,000 drops/s. The shell thickness was accurately controlled by adjusting the ratio of the middle fluid flow rate to the inner fluid flow rate and the drop size decreased with increasing the outer fluid flow rate.